Past, present and future of innovation agencies in Europe - Rainer Kattel (Austrian Foundation for Development Research (ÖFSE), 2024)
The European Union, in the face of mounting geo-political and climate challenges, needs a more effective innovation policy. Currently, its broad experimentalist approach to innovation policies gives Member States and regions autonomy for policy design. However, this often needs more effective organisations and capabilities to take advantage of the policy space. Thus, European countries face quite a substantial rethinking of how innovation policy is designed and implemented through innovation agencies. This policy paper argues that on all levels of European governance, policymakers should pay closer attention to designing and developing organisational ecosystems for innovation, focusing on fostering new capabilities. The paper starts with the assumption that European innovation agencies today face two broad challenges. First, they are tasked with, or engaged in, transforming socio-technical systems (e.g., food, mobility); and second, socio-technical systems fall under over-lapping systems of governance (e.g., food system includes elements from energy, waste management, health, and other policy areas), typically governed by different bodies. The transformation challenge indicates that innovation agencies require a broad spectrum of new capabilities across multiple systems. The governance challenge indicates the need for inter-organisational or distributed capabilities (e.g., division of labour and coordination across multiple organisations). This report discusses how innovation agencies are responding to this dual challenge and what critical steps could be taken to increase their capabilities to tackle the challenges effectively.
Keywords: 330; innovation; governance; innovation agencies; agile stability